THE MOST RADICAL PHILOSOPHER: PUTTING THE CYBER BACK IN SADIE PLANT'S CYBERFEMINISM. - Lê, Vincent (Cosmos & History, 2022)
This article provides a critical introduction to or close reading of British philosopher Sadie Plant's original formulation of cyberfeminism. I begin by showing how Plant's earliest work seeks a form of critique--or what she also calls 'the most radical gesture'--that could never be recuperated by the power structures it seeks to contest as has happened to so much critical thought before. I then argue that her cyberfeminist turn is motivated by the discovery that evermore autonomous machines are carving out a space outside the human spectacle from whence our anthropocentric misconceptions can be eliminated. If Plant characterizes this machinic critique as a feminism, it is because she sees increasingly intelligent machines as harbouring the same attributes often associated with women inasmuch as they have both been traditionally treated as a means to the ends of man without any rational agency, fixed identity or humanity of their own. As we shall see, Plant's cyberfeminism is not so much about emancipating women as it is about emancipating feminine structures like irrationality, fluid identity, general intelligence, and even inhumanity, which she finds incarnated in emerging technologies as they spiral outside of man's control in a purely formal feminism, or even a feminism without women.